2019
DOI: 10.1111/ele.13209
|View full text |Cite
|
Sign up to set email alerts
|

Melanin mitigates the accelerated decay of mycorrhizal necromass with peatland warming

Abstract: Despite being a significant input into soil carbon pools of many high‐latitude ecosystems, little is known about the effects of climate change on the turnover of mycorrhizal fungal necromass. Here, we present results from the first experiment examining the effects of climate change on the long‐term decomposition of mycorrhizal necromass, utilising the Spruce and Peatland Response Under Changing Environments (SPRUCE) experiment. Warming significantly increased necromass decomposition rates but was strongest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 44 publications
4
104
0
1
Order By: Relevance
“…In mixed forests, AM trees may further suffer from reduced nutrient availability and soil acidification. Greater amounts of mycelium may increasingly contribute to soil C sequestration under eCO 2 conditions (Ekblad et al, 2016;Fernandez et al, 2019).…”
Section: (5) Elevated Comentioning
confidence: 99%
“…In mixed forests, AM trees may further suffer from reduced nutrient availability and soil acidification. Greater amounts of mycelium may increasingly contribute to soil C sequestration under eCO 2 conditions (Ekblad et al, 2016;Fernandez et al, 2019).…”
Section: (5) Elevated Comentioning
confidence: 99%
“…Lignin content (Melillo, Aber, & Muratore, 1982;Poorter et al, 2004) Melanin content (Fernandez et al, 2019) Species with higher melanin content will be less susceptible to fungivory and decomposition. They will also sustain slower growth rates and have longer-lasting tissue lifespans.…”
Section: Carbon Allocationmentioning
confidence: 99%
“…It has been hypothesized that the chemically recalcitrant compounds, i. e. for plant litter mainly lignin and lipids and, for the fungal inputs, the abundant polysaccharide chitin, and polymers of phenolic and indolic monomers – melanin (Figure ), form the most stable organic matter . However, some studies have shown that lignin turnover in the soil is more rapid than that of bulk organic matter and degradability of fungal necromass and chitin is also relatively high .…”
Section: How Chemical Structure Affects C Stabilization – Recalcitranmentioning
confidence: 99%
“…Root‐ and fungal‐derived litter compounds provide the most stable organic matter and may potentially affect the decomposition or stabilization rate . For example, decomposition is affected via the quantity and quality of the provided substrate.…”
Section: The Influence Of the Interactions Between Root Litter And Fumentioning
confidence: 99%
See 1 more Smart Citation